Monetary policy transmission mechanism in Indonesia period 2002: Q1 – 2020: Q4: interest rate and asset price channel - Putranto, Laurensius Farel Dwi; Susilo, Y Sri; Sutarta, A Edi (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2023)
This study aims to determine and analyze the effect of the monetary policy transmission mechanism on the interest rate channel and asset prices in Indonesia in achieving the ultimate goal of price stability throughout the period 2002:Q1 – 2020:Q4. This study uses secondary data related to policy interest rate variables, operational target interest rates, information variables, and final target variables for each channel of the monetary policy transmission mechanism. The analytical tool used in this research is the Vector Error Correction Model (VECM) which is processed using statistical software Eviews 10. The results of the analysis on the monetary policy transmission mechanism model of the interest rate channel indicate that in the short term, investment lending variables have a negative and significant effect on The CPI, meanwhile, the investment credit interest rate variable has a negative and significant effect. The results of the long-term analysis of the monetary policy transmission mechanism model of the interest rate channel show that the interest rate for investment credit, consumption credit, and the BI7DRR interest rate have a positive and significant effect on the CPI, while the variables for consumption credit interest rates, investment credit distribution, and real GDP negative and significant effect on the CPI. The results of the VECM analysis for the monetary policy transmission mechanism model for asset price channels confirm that the positive Error Correction Term (ECT) coefficient indicates that there is no adjustment mechanism towards long-term equilibrium. The results of the classical assumption test for the monetary policy transmission mechanism model of asset price channels also confirm deviations in the assumptions of normality and heteroscedasticity. Therefore, the economic interpretation of the VECM estimation on the monetary policy transmission mechanism model of the asset price channel cannot be carried out and requires the use of other analytical tools to produce a valid model .